Teaching mathematics by using application ``Geometer’s Sketchpad’’ - Dagienė, Valentina; Jasutienė , Eglė (Lietuvos matematikos rinkinys, 2004)
This paper analyses is it meaningful to use ``Geometer’s Sketchpad’’ to teach and to learn mathematics at general school of Lithuania. First, it looks how this program helps to implement the goals of National Curricula and Standards. After that, the paper analyses to which group of classification of ICT programs ``Geometer’s Sketchpad’’ can be attached. In addition, it views CD ``Mathematics 9 with geometer’s sketchpad’’ which is prepared for teaching and learning math grade 9th.